2020
DOI: 10.1002/jia2.25528
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for long‐acting Pre‐Exposure Prophylaxis (PrEP) for HIV prevention among South African youth: results of a discrete choice experiment

Abstract: IntroductionExisting biomedical HIV prevention options, though highly effective, present substantial adherence challenges. End‐user input on early‐stage design of new HIV prevention approaches is critical to yielding products that achieve high uptake and adherence. The iPrevent Study examined youths’ preferences for key attributes of long‐acting Pre‐Exposure Prophylaxis (PrEP), with a focus on characteristics pertinent to product delivery alongside key modifiable product attributes.MethodsA discrete choice exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 38 publications
8
70
0
Order By: Relevance
“…There was high inter‐individual variability amongst preferences, underscoring the need for a menu of HIV prevention options, including oral PrEP, vaginal rings, male and female condoms, as well as regular testing and injectable PrEP when available. These results are consistent with the findings of other studies of product preference conducted in young African women [21‐23]. It is also likely that these needs and preferences might change over time as adolescents’ transition to young adulthood.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…There was high inter‐individual variability amongst preferences, underscoring the need for a menu of HIV prevention options, including oral PrEP, vaginal rings, male and female condoms, as well as regular testing and injectable PrEP when available. These results are consistent with the findings of other studies of product preference conducted in young African women [21‐23]. It is also likely that these needs and preferences might change over time as adolescents’ transition to young adulthood.…”
Section: Resultssupporting
confidence: 91%
“…Easy transitions from one option to another would be ideal. It is possible that the efficacy of a product in the prevention of HIV may also affect decision making when these products become available as other studies have reported that highly effective products are more important than other attributes [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Permission was granted from the iPrevent study team to utilize illustrations for public community health clinic and private pharmacy as part of our DCE choice sets [ 34 ]. For the other illustrations the following sources are acknowledged: Daily PreP [ 35 ]; on-demand PrEP [ 36 ]; cost illustrations [ 37 , 38 ]; nausea [ 37 ]; headache [ 39 ]; rash [ 40 ] …”
Section: Resultsmentioning
confidence: 99%
“…Permission was granted from the iPrevent study team to utilize illustrations for public community health clinic and private pharmacy as part of our DCE choice sets [36]. For the other illustrations the following sources are acknowledged: Daily PreP [37]; on-demand PrEP [38]; cost illustrations [39,40]; nausea [39]; headache [41]; rash [42] Pilot testing of the DCE with Community Advisory Board Members…”
Section: Expert Opinionmentioning
confidence: 99%